Enhancement of Quality of Service (QoS) through Improvement of WCDMA Capacity - Imo, F. U.; Nwabueze, C. A.; Aluhumile, Erukpe P. (Darul Yasin Al Sys, 2025)
Achieving maximum customer satisfaction in the Global System for Mobile Communications (GSM) industry has become increasingly challenging due to heightened awareness of consumer rights, population growth, and economic expansion. A critical factor influencing service delivery is network congestion, which significantly impacts the Quality of Service (QoS), a key performance indicator (KPI) used to assess the efficiency of telecommunication services provided to end users. Core metrics for evaluating QoS include accessibility, voice connection quality, and retainability. While various studies have explored methods to mitigate congestion, interference remains a major constraint on the capacity of Wideband Code Division Multiple Access (WCDMA) systems, especially in regions where population density fluctuates, forming high-demand zones or